Challenges Johannesburg non-governmental organisations face in the fight against gender-based violence - Rwebangira, Annelies Byera (My University, 2022)
The purpose of this research is to examine the challenges NGOs in Johannesburg face that hinder the fight against GBV, and to offer recommendations on how to overcome them so as to achieve greater success in their work. A qualitative methodology is used to obtain the findings of the research, with methods of semi-structured interviews and document analysis. The three main challenges facing NGOs dealing with GBV, according to Britton (2006) are shortages in funding, inadequate leadership, and inappropriate methods. This research interrogates these three challenge areas as they relate to GBV. The findings suggest that similar challenges still persist among NGOs as those pointed out by Britton. Shortage in funding is still the leading challenge facing NGOs. Inadequate leadership is continually observed in the form of the limited extent of collaboration of the NGOs with other stakeholders especially the government officials. Lastly, it builds upon the challenges associated with the methods carried out by the NGOs while implementing the strategies, i.e. they are hindered by harmful socio-cultural practices and ethical challenges while carrying out GBV research. In conclusion, the research suggests that NGOs should devise alternative means of securing additional funding, provide more training to enhance leadership, and design methods that are socially and culturally sensitive to the needs of the victims of GBV.
A research report submitted in fulfilment of the requirements for the degree of Master of Management in Public Policy to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, 2022
Keywords: UCTD; SDG-5: Gender equality; Gender; Sexual Violence; Strategies; Success; SDG-5: Gender equality